Scaling field pea technology in dryland areas through a cluster approach: The case of Waghimra zone, Ethiopia - Ademe Mihiretu; Melaku Asresu; Kindye Ayen (PLoS ONE, 2026)
Adoption of improved crop technologies is widely recognized as essential for enhancing agricultural productivity, yet their validation under real farming conditions remains limited. The scaling trial was aimed to provide an interesting agronomic challenge through introducing a new technology that contradicts the established local field production practice. The trial was conducted over four consecutive production years (2019–2022) involving 109 (22 female) purposively selected farmers who managed a collective 32.5 ha of farmland. The farmers were strategically selected to promote the dissemination of new technologies, create demand, strengthen stakeholder linkages, and establish a sustainable technology multiplication system in the area. The comprehensive quantitative and qualitative data were collected and analyzed using proper statistical methods. The results demonstrated that the improved field pea technology was provided a 71.1% yield advantage compared to the existing local practices. With continuous expert support, 75% of farmers applied the full technology package, although 62.5% perceived it as labor-intensive, particularly during planting and thinning stages. Despite this, 95.9% of participants expressed a strong interest in cultivating the new technology in the future. Farmer-to-farmer diffusion was evident, with 1520 kg of improved seed distributed by 75% of involved farmers and stakeholders to non-participant but interested farmers. The farmers and stakeholders who attended different field days were also impressed and committed to adopting the new technology, recognizing its potential adaptation to moisture-deficient areas. These findings hence confirm the agronomic and social viability of the new technology. Therefore, it is recommended that scaling up and out of this improved field pea technology in similar areas be facilitated by the establishment of viable seed-multiplying cooperatives and strengthened stakeholder linkages.